Prosocial Behavior in Toddlerhood: The Contribution of Emotion Knowledge, Theory of Mind, and Language Ability - Brazzelli, Elisa; Pepe, Alessandro; Grazzani, Ilaria (Frontiers in Psychology, 2022)
While there have been attempts to test for the contributions of emotion knowledge, and language abilities to prosocial behavior in toddlerhood, no studies to date have used a multiple battery of direct measures for both these socio-cognitive ability as well as theory of mind on one side, and prosocial behavior on the other side. In contrast, this cross-sectional study evaluated the unique contributions of these variables as antecedents of prosocial conducts in toddlerhood, measuring them via a series of individually administered standardized tasks. Furthermore, given that the existing literature on gender effects documents mixed findings, we set out to explore the role of gender in toddlers’ prosociality. Finally, we also controlled the pattern of association among variables for effects of age. Participants were 127 children aged between 24 and 36 months (M = 29.2 months; SD = 3.5). We found significant correlations among the study variables. In addition, on performing a stepwise multiple regression analysis, we found that emotion knowledge, theory of mind, and language provide the unique contributions of social cognition (SC) abilities to explaining variance in prosocial behaviors (PB). These findings reveal associations between SC and the production of PB as early as toddlerhood and suggest the importance of fostering such abilities from early childhood, with a view to increasing the incidence of prosocial conduct.